Some Body measurements in Shot Putting Using Rotation Method And its Relationship with Achievement in Beginner Students - Jassim, Mohammed (Journal of Physical Education, 2009)
The aim of the research is to identify the relationship between some body measurements in shot putting and rotation method and its relationship with achievement in beginner students. It also aimed at finding the most proper body measurements for this activity. The researcher used the experimental method. the subjects were (25) first year college students/ teaching department/ college of physical education/ University of Baghdad. A questionnaire was designed to select (8) body measurements tests by experts. The researcher used proper statistical methods to treat the results like (standard deviation, mean , Person correlation etc). The researcher concluded the following: 1. There are statistical relation between some body measurements (the height of the body, length of the arm, weight, shoulder width and chest width) and achievement in shot putting using rotation method in beginners. 2. There are no statistical relation in some body measurements (thigh and abdomen girth) and achievement in shot putting by beginners. 3. The research proved the development of beginners in shot putting using rotation method. Finally the researcher recommended the following: 1. The necessity of using body measurements due to their effect on achievement in shot putting using rotation method in beginners. Teaching shot putting using rotation method in all schools and colleges of physical education in Iraq and according to the program proposed by the researcher